Ultra low temperatures in a helium transport vessel: a dilution refrigerator to achieve 30 mK by continuous absorption pumping: Техника свеpхнизких темпеpатуp - Batey, G. J.; White, J. P.; Duncan, W. D.; Simpson, A. F.; Mikheev, V.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
A novel design of dilution refrigerator (DR) is described for continuous operation inside a transport Dewar with a neck diameter more than 51 mm. The time required for cooling the mixing chamber from room temperature to 30 mK is 3.5-4.5 h. Warming up to 300 K reguires 0.5-1.0 h. The cooling power achieved is 40 mikroW at 100 mK. The DR is fitted with 6 mm line of sight access down to the mixing chamber. A distinguishing feature of this refrigerator is the absence of a traditional gas handling system, which makes it easy to transport in a small car and quickly commission in a new laboratory within a few hours.